Emulsion of battery negative electrode ceramic slurry for new energy automobile and preparation method of emulsion

By introducing modified sodium carboxymethylcellulose and styrene butadiene emulsion into the negative electrode material of the battery, the problems of insufficient structural stability and limited conductivity of the traditional battery negative electrode material are solved, which significantly improves the flexibility, dispersion stability and conductivity of the battery, extends the cycle life of the battery and improves the high-temperature capacity retention rate.

CN119695394AActive Publication Date: 2025-03-25河北昊泽化工有限公司
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510191585.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-25
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

The structural stability of traditional battery negative electrode materials is insufficient during the high-rate charging and discharging process, resulting in rapid attenuation of capacity, affecting the cycle life of the battery, and limited conductivity, limiting the charging and discharging efficiency of the battery and unable to meet the needs of fast charging of new energy vehicles.

Method used

Modified sodium carboxymethylcellulose was prepared through three-step chemical reaction, and long-chain alkyl groups, amide groups and ester groups were introduced to enhance the adhesion with the active material, improve the flexibility and dispersion stability of the slurry, and cooperate with styrene butadiene emulsion, graphite powder, etc. to optimize rheology characteristics and improve coating uniformity.

Benefits of technology

It significantly improves the flexibility and dispersion stability of the negative electrode ceramic slurry of the battery, ensures the overall performance of the electrode sheet, improves the high-temperature capacity retention rate of the battery and the conductivity of the electrode sheet, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of battery negative electrode ceramic slurry, and particularly relates to an emulsion of battery negative electrode ceramic slurry for a new energy automobile and a preparation method of the emulsion. The emulsion is prepared from the following raw materials in parts by weight: 80 to 90 parts of graphite powder, 7 to 13 parts of aluminum oxide powder, 1 to 3 parts of styrene-butadiene emulsion and 0.4 to 0.7 part of modified sodium carboxymethyl cellulose; the styrene-butadiene emulsion is prepared from styrene, butadiene, acrylic acid, itaconic acid, tert-dodecanethiol, sodium dodecyl benzene sulfonate, alkylphenol polyoxyethylene ether sodium sulfate and other raw materials. The styrene-butadiene emulsion, the modified sodium carboxymethyl cellulose, the graphite powder and other raw materials have a synergistic effect, so that the rheological property of the slurry is optimized, and the comprehensive performance of the pole piece is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode ceramic slurry, and specifically relates to an emulsion of battery negative electrode ceramic slurry for new energy vehicles and a preparation method thereof. Background Art

[0002] In the field of new energy vehicles, battery performance is one of the key factors that determine the overall performance of the vehicle. With the rapid development of the new energy vehicle market, higher and higher requirements are put forward for the energy density, charge and discharge efficiency, cycle life and safety of batteries. As an important component of the battery, the performance of the battery negative electrode material directly affects the various performance indicators of the battery. In the face of the growing performance requirements, traditional battery negative electrode materials have gradually exposed some limitations. For example, during high-rate charge and discharge, the structural stability of the electrode material is insufficient, which easily leads to rapid capacity decay and affects the cycle life of the battery; in addition, the conductivity of some negative electrode materials is limited, which to a certain extent limits the charge and discharge efficiency of the battery and cannot meet the needs of new energy vehicles in terms of fast charging. In order to overcome these problems, researchers began to explore new negative electrode materials and preparation technologies. Ceramic materials have gradually been introduced into the research of battery negative electrode materials due to their unique physical and chemical properties, such as high hardness, high chemical stability, and good high temperature resistance.

[0003] The patent with application number CN201811568275.X provides a negative electrode composite slurry and a preparation method thereof, and a negative electrode plate of a lithium battery. The negative electrode composite slurry is made of ultrafine glass fiber, ceramic powder, binder 1, binder 2, styrene-butadiene emulsion or styrene-acrylic emulsion and water in a certain proportion. The composite slurry is used to prepare the negative electrode plate of a lithium battery, which can effectively improve the safety performance of the lithium battery. By mixing ultrafine glass fiber and ceramic powder in the negative electrode composite slurry, the two are evenly dispersed to form a negative electrode composite coating with a three-dimensional structure, which not only ensures the heat insulation effect, but also has a good lithium ion transmission effect, reduces the problem of blockage of lithium ion diffusion channels, and ensures the rate performance of the lithium battery. The experimental results show that the lithium battery using the negative electrode composite slurry has significantly improved safety in the acupuncture test, and the capacity retention rate is also significantly better than the control battery without adding ultrafine glass fiber. As a binder material used in the negative electrode of lithium batteries, although the amount of styrene butadiene emulsion in the lithium battery negative electrode material system is small, it plays a pivotal role in battery performance. In view of the fact that lithium batteries will be used in various complex environments, from high temperature to low temperature, from high humidity to severe mechanical vibration scenarios, the industry has put forward more stringent requirements on the various indicators of styrene butadiene emulsion. The patent with application number CN202110355747.9 provides a method for preparing a ceramic slurry, a ceramic diaphragm and a lithium-ion battery. The method for preparing the ceramic slurry is to add and disperse the stabilizer, dispersant, ceramic powder, etc. in sequence through specific steps, use a sand mill to process, and finally add a wetting agent to obtain a ceramic slurry; the slurry prepared by this method has good stability, uniform dispersion, and is not easy to stratify or agglomerate. The ceramic diaphragm prepared using the slurry is obtained by coating and baking on the base film, and has high air permeability and good heat resistance. The safety performance of the lithium-ion battery containing this diaphragm is significantly improved, and the service life is extended. The experimental results show that compared with the comparative method, the slurry prepared by the inventive method has better stability, dispersion uniformity and wettability, and the ceramic diaphragm prepared has better air permeability. However, sodium carboxymethyl cellulose can play an important role in ceramic slurry as a stabilizer, but there are also some potential disadvantages. The flexibility of sodium carboxymethyl cellulose is relatively poor, which will cause cracks or uneven coating layers in the slurry during the coating process, thereby affecting the overall performance of the ceramic diaphragm. In addition, under different pH values ​​or ionic strengths, the solubility and stability of sodium carboxymethyl cellulose will change, which will cause slurry to be stratified or precipitated during storage or use, affecting the uniformity and stability of the slurry. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an emulsion of ceramic slurry for negative electrode of batteries for new energy vehicles and a preparation method thereof, wherein modified sodium carboxymethyl cellulose is prepared by a three-step chemical reaction, and the bonding force with the active material is enhanced by introducing long-chain alkyl groups, amide groups and ester groups, thereby improving the flexibility and dispersion stability of the slurry; the modified sodium carboxymethyl cellulose synergistically acts with styrene-butadiene emulsion, graphite powder, etc. to optimize the rheological properties, improve the coating uniformity, and ensure the overall performance of the electrode.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 80-90 parts of graphite powder, 7-13 parts of alumina powder, 1-3 parts of styrene-butadiene emulsion, and 0.4-0.7 parts of modified sodium carboxymethyl cellulose; The styrene-butadiene emulsion comprises the following raw materials in parts by weight: 25-35 parts of styrene, 20-25 parts of butadiene, 1-3 parts of acrylic acid, 0.5-1 parts of itaconic acid, 0.2-0.5 parts of tert-dodecyl mercaptan, 0.4-0.6 parts of sodium dodecylbenzene sulfonate, 0.5-2 parts of sodium alkylphenol polyoxyethylene ether sulfate, 1-2 parts of acrylamide, 0.4-1 parts of sodium persulfate, 0.1-1 parts of solid alkali, 0.1-0.2 parts of liquid alkali, 40-50 parts of water, 0.5-1.0 parts of defoaming agent and 0.5-1.0 parts of preservative.

[0006] Furthermore, the preparation method of the modified sodium carboxymethyl cellulose is: S1. Disperse methyl oleate in anhydrous ethanol under nitrogen atmosphere and stirring, add ethanolamine, mix well, and then dropwise add sodium methoxide methanol solution. The addition is completed within 0.5-1.5 hours, and the temperature is raised to 40-60° C., react for 6-8 hours, and then cool and purify to obtain an intermediate; S2. Disperse 2,5-dimethylhexanoic acid in N,N-dimethylformamide under stirring, add the intermediate obtained in step S1 and p-toluenesulfonic acid, raise the temperature to 75-95° C., react for 6-10 hours, and obtain modified oleic acid ester by cooling and purification; S3, dispersing sodium carboxymethyl cellulose in deionized water, stirring at 55-65°C until dissolved, cooling to room temperature, and then dropping potassium persulfate aqueous solution, the dropping is completed in 40-60 minutes, and stirring is continued for 10-20 minutes, and then adding the modified oleic acid ester obtained in step S2, heating to 70-90°C, stirring and reacting for 2-4 hours, cooling and purifying to obtain modified sodium carboxymethyl cellulose; Wherein, the synthetic route of modified oleic acid ester is as follows: ; .

[0007] The invention uses methyl oleate and ethanolamine as starting materials, and obtains an intermediate under the catalytic action of sodium methoxide; then uses the intermediate and 2,5-dimethylhexanoic acid as raw materials, and obtains modified oleic acid ester under the action of p-toluenesulfonic acid; finally uses the modified oleic acid ester as a modifier, and chemically grafts sodium carboxymethyl cellulose under the action of potassium persulfate to obtain modified sodium carboxymethyl cellulose.

[0008] In order to functionalize sodium carboxymethyl cellulose, the mass ratio of methyl oleate to ethanolamine in step S1 is 10-15:4, the amount of methyl oleate added to the anhydrous ethanol is 0.15-0.20 g / mL, the volume ratio of anhydrous ethanol to sodium methoxide methanol solution is 40:5-10, and the molar concentration of the sodium methoxide methanol solution is 3.5-4.5 mol / L; the mass ratio of 2,5-dimethylhexanoic acid, intermediate, and p-toluenesulfonic acid in step S2 is 2-3:5:0.08 -0.12, the amount of 2,5-dimethylhexanoic acid added to N,N-dimethylformamide is 0.18-0.26 g / mL; the mass ratio of sodium carboxymethyl cellulose and modified oleate in step S3 is 1:0.5-0.8, the amount of sodium carboxymethyl cellulose added to the deionized water is 0.08-0.11 g / mL, the volume ratio of the deionized water and the potassium persulfate aqueous solution is 10:0.3-0.5, and the molar concentration of the potassium persulfate aqueous solution is 0.09-0.11 mol / L.

[0009] Furthermore, the defoaming agent is polydimethylsiloxane; the preservative is one or more of phenoxyethanol, ethylhexylglycerin, and p-hydroxybenzoic acid.

[0010] Further, the preparation method of the styrene-butadiene emulsion is: (1) Add acrylic acid, solid alkali, and 0.15-0.25 parts of sodium dodecylbenzene sulfonate to 22-26 parts of water, and stir until dissolved to obtain an aqueous phase; (2) adding tert-dodecyl mercaptan to 20-23 parts of styrene and stirring for 20-40 minutes to obtain an oil phase; (3) Under stirring conditions, add alkylphenol polyoxyethylene ether sodium sulfate, acrylamide, itaconic acid, 0.5-2.5 parts of butadiene, the remaining sodium dodecylbenzene sulfonate and the remaining styrene to the remaining water, and after vacuuming, heat to 75-80°C, add 0.2-0.3 parts of sodium persulfate, react at 93-97°C for 20-40 minutes, then add water phase, oil phase, the remaining sodium persulfate and the remaining butadiene, keep warm at 95-100°C for 0.5-1.5 hours, finally add liquid alkali, and add 0.2-0.4 parts of defoaming agent for physical degassing, cool naturally to 45°C, add preservatives and the remaining defoaming agent, mix well, filter, and discharge to obtain the product.

[0011] The present invention also provides a method for preparing an emulsion of anode ceramic slurry for batteries for new energy vehicles, comprising the following steps: dispersing modified sodium carboxymethyl cellulose in deionized water, stirring at 60-70°C until dissolved, cooling to room temperature, adding styrene-butadiene emulsion, and stirring for 15-25 minutes to obtain a mixed emulsion; mechanically mixing graphite powder and alumina powder in the solid phase to obtain a mixed powder; adding the mixed emulsion to the mixed powder, stirring for 40-60 minutes, then grinding, sieving, and removing bubbles in a vacuum to obtain the mixed powder.

[0012] The present invention has the following beneficial effects: The present invention uses a three-step method to introduce long-chain alkyl, amide group and ester group into the molecular structure of sodium carboxymethyl cellulose, which significantly improves its performance in the battery negative electrode ceramic slurry emulsion. The introduction of long-chain alkyl builds a "flexible bridge" between molecular chains, which can increase the activity space between molecular chains, weaken the binding force between molecular chains, and can move and deform more freely. During the rolling and bending of the pole piece, the molecular chain can better adapt to the external force through this free movement, thereby reducing the occurrence of brittle fracture and greatly improving the flexibility of the sodium carboxymethyl cellulose-based composite material. The introduction of long-chain alkyl and amide groups changes the surface properties of the slurry system. The long-chain alkyl group enhances the interaction with the active substance by virtue of its own structural characteristics, making the slurry more evenly dispersed. The amide group can be adsorbed on the surface of the active material particles through its own polarity and steric hindrance, preventing the particles from aggregating due to mutual attraction. The two groups work together to increase the surface energy of the slurry and reduce the aggregation phenomenon between particles, thereby improving the dispersion stability of the slurry. In addition, the amide group has a high polarity, which can not only form hydrogen bonds with functional groups such as hydroxyl and carboxyl on the surface of the current collector to improve the bonding performance of the composite slurry, but also form a hydrogen bond network between modified sodium carboxymethyl cellulose molecules to enhance the intermolecular force. When subjected to external force, the network can disperse stress and avoid the active material from falling off the current collector due to local stress concentration, thereby further improving the bonding performance and peel strength of the composite slurry.

[0013] Modified sodium carboxymethyl cellulose can improve the system's bonding performance, and styrene butadiene emulsion is used as a binder supplement. Together, the two firmly bind and attach graphite powder, alumina powder, etc. to the current collector, forming a stable electrode structure, reducing the shedding and loss of active substances, thereby ensuring the normal embedding and extraction of lithium ions, and thereby improving the high-temperature capacity retention rate of the pole piece. Modified sodium carboxymethyl cellulose works synergistically with styrene butadiene emulsion and other additives to evenly disperse the active materials in the slurry, avoid agglomeration and sedimentation, ensure the uniformity and stability of the slurry, optimize the coating process, and ensure the consistency of the pole piece. When modified sodium carboxymethyl cellulose is used in combination with other materials and coated on the surface of the current collector, it can form a denser film structure, improve the conductivity of the pole piece, and thus help reduce the resistivity of the pole piece. DETAILED DESCRIPTION

[0014] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0015] Sodium carboxymethyl cellulose, density 1.6g / cm³, melting point 274℃, purchased from Baiyundu Biotechnology Co., Ltd.; graphite powder, mesh number 1000, fixed carbon content 99.99%, model PWGX-22 (1000), purchased from Jiaxing Naco New Materials Co., Ltd.; alumina powder, mesh number 800, model JC-A30P, purchased from Qinghe Chaotai Metal Materials Co., Ltd.; alkylphenol polyoxyethylene ether sodium sulfate, active substance content 80%, model OP4SA, purchased from Nantong Arches Chemical Co., Ltd.; polydimethylsiloxane, model 201, purchased from Jinan Yingyu Chemical Co., Ltd. The raw materials used in the following examples are all common commercially available products. Example 1

[0016] An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 85 parts of graphite powder, 11 parts of alumina powder, 2 parts of styrene-butadiene emulsion, and 0.6 parts of modified sodium carboxymethyl cellulose; The preparation method of the modified sodium carboxymethyl cellulose is: S1. In a nitrogen atmosphere and under stirring conditions, methyl oleate is dispersed in anhydrous ethanol, ethanolamine is added, mixed evenly, and then sodium methoxide methanol solution is added dropwise. The addition is completed in 1 hour, the temperature is raised to 50°C, and the reaction is performed for 7 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, and the mixture is subjected to reduced pressure distillation and vacuum drying to obtain an intermediate; wherein the mass ratio of the methyl oleate to the ethanolamine is 12:4, the amount of methyl oleate added to the anhydrous ethanol is 0.18 g / mL, the volume ratio of the anhydrous ethanol to the sodium methoxide methanol solution is 40:7, and the molar concentration of the sodium methoxide methanol solution is 4 mol / L; S2, under stirring conditions, disperse 2,5-dimethylhexanoic acid in N,N-dimethylformamide, then add the intermediate obtained in step S1 and p-toluenesulfonic acid, heat to 85°C, react for 8h, naturally cool to room temperature, add saturated sodium bicarbonate aqueous solution, continue stirring for 40min, then add ethyl acetate for extraction, separate the liquids to obtain an ester phase, and distill under reduced pressure and dry in vacuo to obtain a modified oleate; wherein the mass ratio of the 2,5-dimethylhexanoic acid, the intermediate, and p-toluenesulfonic acid is 2.5:5:0.1, the amount of 2,5-dimethylhexanoic acid added to N,N-dimethylformamide is 0.22g / mL, and the volume ratio of N,N-dimethylformamide, saturated sodium bicarbonate aqueous solution, and ethyl acetate is 1:1:2; The NMR results of modified oleic acid ester are: 1 H NMR (300MHz, DMSO-d6) δ 8.01 (s, 1H), 5.43 (t, 2H), 4.34 (t, 2H), 3.28 (t, 2H), 2.32-2.35 (m, 1H), 2.13-2.16 ( m, 6H), 1.55-1.60 (m, 5H), 1.26-1.30 (m, 20H), 1.12-1.16 (m, 5H), 0.88-0.91 (m, 9H); S3, dispersing sodium carboxymethyl cellulose in deionized water, stirring at 60°C until dissolved, cooling naturally to room temperature, and then dripping potassium persulfate aqueous solution, the dripping is completed within 50 minutes, stirring is continued for 15 minutes, and then the modified oleic acid ester obtained in step S2 is added, the temperature is raised to 80°C, stirring for reaction for 3 hours, cooling naturally to room temperature, precipitating and separating with 95% ethanol, extracting with acetone in a Soxhlet extractor for 10 hours after drying, and vacuum drying to obtain modified sodium carboxymethyl cellulose, the grafting rate of modified sodium carboxymethyl cellulose is 23.6%; wherein the mass ratio of sodium carboxymethyl cellulose to modified oleic acid ester is 1:0.7, the amount of sodium carboxymethyl cellulose added in the deionized water is 0.09 g / mL, the volume ratio of deionized water to potassium persulfate aqueous solution is 10:0.4, and the molar concentration of the potassium persulfate aqueous solution is 0.1 mol / L. The calculation formula of the grafting rate of modified sodium carboxymethyl cellulose is: grafting rate (%) = (modified sodium carboxymethyl cellulose output-sodium carboxymethyl cellulose feed amount) / sodium carboxymethyl cellulose feed amount × 100%.

[0017] The styrene-butadiene emulsion comprises the following raw materials in parts by weight: 30 parts of styrene, 20 parts of butadiene, 1 part of acrylic acid, 0.5 parts of itaconic acid, 0.2 parts of tert-dodecyl mercaptan, 0.5 parts of sodium dodecylbenzene sulfonate, 0.5 parts of sodium sulfate of alkylphenol polyoxyethylene ether, 1 part of acrylamide, 0.5 parts of sodium persulfate, 0.3 parts of solid alkali, 0.2 parts of liquid alkali, 48 parts of water, 0.5 parts of defoamer, and 0.5 parts of preservative; the defoamer is polydimethylsiloxane, and the preservative is phenoxyethanol; The preparation method of styrene butadiene emulsion is: (1) Prepare the aqueous phase: add 24 parts of water to the reactor, start stirring, then add acrylic acid, caustic soda, and 0.2 parts of sodium dodecylbenzene sulfonate, and stir for 1 hour until all are dissolved; (2) Preparation of oil phase: Add 23 parts of styrene to the reactor, start stirring, add tert-dodecyl mercaptan, and stir for 30 minutes; (3) Add the remaining water to the reactor, start stirring, add sodium alkylphenol polyoxyethylene ether sulfate, acrylamide, itaconic acid, 1.5 parts of butadiene, the remaining sodium dodecylbenzene sulfonate and the remaining styrene, then evacuate the reactor to -0.07MPa, fill it with nitrogen to 0MPa, evacuate it to -0.07MPa again, raise the temperature to 78°C, quickly add 0.2 parts of sodium persulfate, control the reaction temperature at 95°C, and react for 30 minutes, then feed the water phase, oil phase, and the remaining persulfate. Sodium sulfate and the remaining butadiene, the feeding temperature is controlled at 90 ° C, the feeding time is 4.5h, and after the feeding is completed, it is kept warm at 98 ° C for 1h, liquid alkali is added to adjust the pH value, and 0.3 parts of defoaming agent are added for physical degassing, and the temperature is naturally reduced to 45 ° C, a preservative and the remaining defoaming agent are added, mixed evenly, filtered through a 325-mesh sieve, and discharged to obtain; the solid content of the styrene-butadiene emulsion prepared in this embodiment is 50%, the viscosity is less than 300cp, the particle size is 120-160nm, and the pH is 6-7.

[0018] A method for preparing an emulsion of anode ceramic slurry for a battery for new energy vehicles comprises the following steps: dispersing modified sodium carboxymethyl cellulose in deionized water, stirring at 65° C. until dissolved, cooling to room temperature, adding styrene butadiene emulsion, stirring at 250 rpm for 20 min, to obtain a mixed emulsion; mechanically solid-phase mixing graphite powder and alumina powder, stirring at a speed of 40 rpm for 20 min, to obtain a mixed powder; adding the mixed emulsion to the mixed powder, stirring at 450 rpm for 50 min, and then ball milling, using zirconium oxide balls for ball milling, the diameter of the zirconium oxide balls is 2.0 mm, the rotation speed of the ball milling is 40 rpm, the ball milling time is 3 h, the ball-to-material ratio is 4:1, and after ball milling, passing through a 325-mesh sieve, and vacuum removing bubbles to obtain the product; wherein the mass ratio of modified sodium carboxymethyl cellulose to deionized water is 0.6:70. Example 2

[0019] An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 80 parts of graphite powder, 7 parts of alumina powder, 1 part of styrene-butadiene emulsion, and 0.4 parts of modified sodium carboxymethyl cellulose; The preparation method of the modified sodium carboxymethyl cellulose is: S1. In a nitrogen atmosphere and under stirring conditions, methyl oleate is dispersed in anhydrous ethanol, ethanolamine is added, mixed evenly, and then a methanol solution of sodium methoxide is added dropwise, and the addition is completed in 0.5 h. The temperature is raised to 60 ° C. and the reaction is performed for 6 h. After the reaction is completed, the mixture is naturally cooled to room temperature, and the mixture is subjected to reduced pressure distillation and vacuum drying to obtain an intermediate; wherein the mass ratio of the methyl oleate to the ethanolamine is 10:4, the amount of methyl oleate added to the anhydrous ethanol is 0.15 g / mL, the volume ratio of the anhydrous ethanol to the methanol solution of sodium methoxide is 40:5, and the molar concentration of the methanol solution of sodium methoxide is 3.5 mol / L; S2, under stirring conditions, disperse 2,5-dimethylhexanoic acid in N,N-dimethylformamide, then add the intermediate obtained in step S1 and p-toluenesulfonic acid, heat to 95°C, react for 6h, naturally cool to room temperature, add saturated sodium bicarbonate aqueous solution, continue stirring for 40min, then add ethyl acetate for extraction, separate the liquids to obtain an ester phase, and distill under reduced pressure and dry in vacuo to obtain a modified oleate; wherein the mass ratio of the 2,5-dimethylhexanoic acid, the intermediate, and p-toluenesulfonic acid is 2:5:0.08, the amount of 2,5-dimethylhexanoic acid added to N,N-dimethylformamide is 0.18g / mL, and the volume ratio of N,N-dimethylformamide, saturated sodium bicarbonate aqueous solution, and ethyl acetate is 1:1:2; S3, dispersing sodium carboxymethyl cellulose in deionized water, stirring at 65°C until dissolved, cooling naturally to room temperature, and then dripping potassium persulfate aqueous solution, the dripping is completed in 40 minutes, stirring is continued for 10 minutes, and then the modified oleic acid ester obtained in step S2 is added, the temperature is raised to 90°C, stirring for reaction for 2 hours, cooling naturally to room temperature, precipitating and separating with 95% ethanol, extracting with acetone in a Soxhlet extractor for 10 hours after drying, and vacuum drying to obtain modified sodium carboxymethyl cellulose, the grafting rate of modified sodium carboxymethyl cellulose is 23.6%; wherein the mass ratio of sodium carboxymethyl cellulose to modified oleic acid ester is 1:0.5, the amount of sodium carboxymethyl cellulose added in the deionized water is 0.08 g / mL, the volume ratio of deionized water to potassium persulfate aqueous solution is 10:0.3, and the molar concentration of the potassium persulfate aqueous solution is 0.09 mol / L. The calculation formula of the grafting rate of modified sodium carboxymethyl cellulose is: grafting rate (%) = (modified sodium carboxymethyl cellulose output-sodium carboxymethyl cellulose feed amount) / sodium carboxymethyl cellulose feed amount × 100%.

[0020] The styrene-butadiene emulsion comprises the following raw materials in parts by weight: 25 parts of styrene, 25 parts of butadiene, 2 parts of acrylic acid, 0.4 parts of itaconic acid, 0.5 parts of tert-dodecyl mercaptan, 0.4 parts of sodium dodecylbenzene sulfonate, 1 part of sodium sulfate of alkylphenol polyoxyethylene ether, 2 parts of acrylamide, 0.8 parts of sodium persulfate, 0.6 parts of solid alkali, 0.1 parts of liquid alkali, 44 parts of pure water, 0.8 parts of defoamer, and 0.7 parts of preservative; the defoamer is polydimethylsiloxane, and the preservative is ethylhexylglycerin; The preparation method of styrene butadiene emulsion is: (1) Prepare the aqueous phase: add 22 parts of water to the reactor, start stirring, then add acrylic acid, caustic soda, and 0.15 parts of sodium dodecylbenzene sulfonate, and stir for 1 hour until all are dissolved; (2) Preparation of oil phase: Add 20 parts of styrene to the reactor, start stirring, add tert-dodecyl mercaptan, and stir for 20 minutes; (3) Add the remaining water to the reactor, start stirring, add sodium alkylphenol polyoxyethylene ether sulfate, acrylamide, itaconic acid, 0.5 parts of butadiene, the remaining sodium dodecylbenzene sulfonate and the remaining styrene, then evacuate the reactor to -0.07MPa, fill with nitrogen to 0MPa, evacuate to -0.07MPa again, raise the temperature to 75°C, quickly add 0.3 parts of sodium persulfate, control the reaction temperature at 93°C, and react for 40 minutes, then feed the water phase, oil phase, and the remaining persulfate. Sodium and remaining butadiene, the feeding temperature is controlled at 90°C, the feeding time is 4.5h, and after the feeding is completed, it is kept warm at 95°C for 1.5h, liquid alkali is added to adjust the pH value, and 0.2 parts of defoaming agent are added for physical degassing, and the temperature is naturally reduced to 45°C, a preservative and the remaining defoaming agent are added, mixed evenly, filtered through a 325-mesh sieve, and discharged to obtain; the solid content of the styrene-butadiene emulsion prepared in this embodiment is 50.5%, the viscosity is less than 300cp, the particle size is 120-160nm, and the pH is 6-7.

[0021] A method for preparing an emulsion of anode ceramic slurry for a battery for new energy vehicles comprises the following steps: dispersing modified sodium carboxymethyl cellulose in deionized water, stirring at 70°C until dissolved, cooling to room temperature, adding styrene butadiene emulsion, stirring at 250rpm for 15min to obtain a mixed emulsion; mechanically solid-phase mixing graphite powder and alumina powder at a stirring speed of 40rpm for 20min to obtain a mixed powder; adding the mixed emulsion to the mixed powder, stirring at 450rpm for 40min, and then ball milling, using zirconium oxide balls for ball milling, the diameter of the zirconium oxide balls is 2.0mm, the rotation speed of the ball milling is 40rpm, the ball milling time is 3h, the ball-to-material ratio is 4:1, and after ball milling, passing through a 325-mesh sieve, and vacuum removing bubbles to obtain the product; wherein the mass ratio of modified sodium carboxymethyl cellulose to deionized water is 0.6:70. Example 3

[0022] An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 90 parts of graphite powder, 13 parts of alumina powder, 3 parts of styrene-butadiene emulsion, and 0.7 parts of modified sodium carboxymethyl cellulose; The preparation method of the modified sodium carboxymethyl cellulose is: S1. In a nitrogen atmosphere and under stirring conditions, methyl oleate is dispersed in anhydrous ethanol, ethanolamine is added, mixed evenly, and then a methanol solution of sodium methoxide is added dropwise. The addition is completed in 1.5 hours, the temperature is raised to 40°C, and the reaction is performed for 8 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, and the mixture is subjected to reduced pressure distillation and vacuum drying to obtain an intermediate; wherein the mass ratio of the methyl oleate to the ethanolamine is 15:4, the amount of methyl oleate added to the anhydrous ethanol is 0.2 g / mL, the volume ratio of the anhydrous ethanol to the methanol solution of sodium methoxide is 40:10, and the molar concentration of the methanol solution of sodium methoxide is 4.5 mol / L; S2, under stirring conditions, 2,5-dimethylhexanoic acid is dispersed in N,N-dimethylformamide, and then the intermediate obtained in step S1 and p-toluenesulfonic acid are added, the temperature is raised to 75°C, the reaction is carried out for 10 hours, and the mixture is naturally cooled to room temperature, a saturated sodium bicarbonate aqueous solution is added, stirring is continued for 40 minutes, and then ethyl acetate is added for extraction, and the liquid is separated to obtain an ester phase, and the ester phase is subjected to reduced pressure distillation and vacuum drying to obtain a modified oleic acid ester; wherein the mass ratio of the 2,5-dimethylhexanoic acid, the intermediate, and p-toluenesulfonic acid is 3:5:0.12, the amount of 2,5-dimethylhexanoic acid added to N,N-dimethylformamide is 0.26 g / mL, and the volume ratio of N,N-dimethylformamide, saturated sodium bicarbonate aqueous solution, and ethyl acetate is 1:1:2; S3, dispersing sodium carboxymethyl cellulose in deionized water, stirring at 55°C until dissolved, cooling naturally to room temperature, and then dripping potassium persulfate aqueous solution, the dripping is completed within 60 minutes, stirring is continued for 20 minutes, and then the modified oleic acid ester obtained in step S2 is added, the temperature is raised to 70°C, stirring for reaction for 4 hours, cooling naturally to room temperature, precipitating and separating with 95% ethanol, extracting with acetone in a Soxhlet extractor for 10 hours after drying, and vacuum drying to obtain modified sodium carboxymethyl cellulose, the grafting rate of modified sodium carboxymethyl cellulose is 23.6%; wherein the mass ratio of sodium carboxymethyl cellulose to modified oleic acid ester is 1:0.8, the amount of sodium carboxymethyl cellulose added in the deionized water is 0.11 g / mL, the volume ratio of deionized water to potassium persulfate aqueous solution is 10:0.5, and the molar concentration of the potassium persulfate aqueous solution is 0.11 mol / L. The calculation formula of the grafting rate of modified sodium carboxymethyl cellulose is: grafting rate (%) = (modified sodium carboxymethyl cellulose output-sodium carboxymethyl cellulose feed amount) / sodium carboxymethyl cellulose feed amount × 100%.

[0023] The styrene-butadiene emulsion comprises the following raw materials in parts by weight: 35 parts of styrene, 25 parts of butadiene, 3 parts of acrylic acid, 1 part of itaconic acid, 0.5 parts of tert-dodecyl mercaptan, 0.6 parts of sodium dodecylbenzene sulfonate, 1.5 parts of sodium sulfate of alkylphenol polyoxyethylene ether, 1.5 parts of acrylamide, 0.4 parts of sodium persulfate, 0.1 parts of solid alkali, 0.8 parts of liquid alkali, 50 parts of pure water, 1 part of defoamer, and 1 part of preservative; the defoamer is polydimethylsiloxane, and the preservative is p-hydroxybenzoic acid; The preparation method of styrene butadiene emulsion is: (1) Prepare the aqueous phase: add 26 parts of water to the reactor, start stirring, then add acrylic acid, caustic soda, and 0.25 parts of sodium dodecylbenzene sulfonate, and stir for 1 hour until all are dissolved; (2) Preparation of oil phase: Add 23 parts of styrene to the reactor, start stirring, add tert-dodecyl mercaptan, and stir for 40 minutes; (3) Add the remaining water to the reactor, start stirring, add sodium alkylphenol polyoxyethylene ether sulfate, acrylamide, itaconic acid, 2.5 parts of butadiene, the remaining sodium dodecylbenzene sulfonate and the remaining styrene, then evacuate the reactor to -0.07MPa, fill it with nitrogen to 0MPa, evacuate it to -0.07MPa again, raise the temperature to 80°C, quickly add 0.25 parts of sodium persulfate, control the reaction temperature at 97°C, and react for 20 minutes, then feed the water phase, oil phase, and the remaining persulfate. Sodium and remaining butadiene, the feeding temperature is controlled at 90°C, the feeding time is 4.5h, and after the feeding is completed, it is kept warm at 100°C for 0.5h, liquid alkali is added to adjust the pH value, and 0.4 parts of defoaming agent are added for physical degassing, and the temperature is naturally reduced to 45°C, a preservative and the remaining defoaming agent are added, mixed evenly, filtered through a 325-mesh sieve, and discharged to obtain; the solid content of the styrene-butadiene emulsion prepared in this embodiment is 49.5%, the viscosity is less than 300cp, the particle size is 120-160nm, and the pH is 6-7.

[0024] A method for preparing an emulsion of anode ceramic slurry for a battery for new energy vehicles comprises the following steps: dispersing modified sodium carboxymethyl cellulose in deionized water, stirring at 60°C until dissolved, cooling to room temperature, adding styrene butadiene emulsion, stirring at 250rpm for 25min to obtain a mixed emulsion; mechanically solid-phase mixing graphite powder and alumina powder at a stirring speed of 40rpm for 20min to obtain a mixed powder; adding the mixed emulsion to the mixed powder, stirring at 450rpm for 60min, and then ball milling, using zirconium oxide balls for ball milling, the diameter of the zirconium oxide balls is 2.0mm, the rotation speed of the ball milling is 40rpm, the ball milling time is 3h, the ball-to-material ratio is 4:1, and after ball milling, passing through a 325-mesh sieve, and vacuum removing bubbles to obtain the product; wherein the mass ratio of modified sodium carboxymethyl cellulose to deionized water is 0.6:70. Example 4

[0025] An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 83 parts of graphite powder, 10 parts of alumina powder, 2 parts of styrene-butadiene emulsion prepared in Example 1, and 0.5 parts of modified sodium carboxymethyl cellulose prepared in Example 1.

[0026] A method for preparing an emulsion of anode ceramic slurry for a battery for new energy vehicles comprises the following steps: dispersing modified sodium carboxymethyl cellulose in deionized water, stirring at 65°C until dissolved, cooling to room temperature, adding styrene butadiene emulsion, stirring at 250rpm for 22min to obtain a mixed emulsion; mechanically solid-phase mixing graphite powder and aluminum oxide powder at a stirring speed of 40rpm for 30min to obtain a mixed powder; adding the mixed emulsion to the mixed powder, stirring at 450rpm for 55min, and then ball milling, using zirconium oxide balls for ball milling, the diameter of the zirconium oxide balls is 2.0mm, the rotation speed of the ball milling is 40rpm, the ball milling time is 3h, the ball-to-material ratio is 4:1, and after ball milling, passing through a 325-mesh sieve, and vacuum removing bubbles to obtain the product; wherein the mass ratio of modified sodium carboxymethyl cellulose to deionized water is 0.6:70. Comparative Example 1

[0027] An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 85 parts of graphite powder, 11 parts of alumina powder, 0.7 parts of sodium carboxymethyl cellulose, and 2 parts of the styrene-butadiene emulsion prepared in Example 1.

[0028] A method for preparing an emulsion of anode ceramic slurry for batteries for new energy vehicles is prepared according to the method described in Example 1. Comparative Example 2

[0029] An emulsion of anode ceramic slurry for a new energy vehicle battery comprises the following raw materials in parts by weight: 85 parts of graphite powder, 11 parts of alumina powder, 0.7 parts of modified sodium carboxymethyl cellulose prepared in Example 1, and 3 parts of common commercially available styrene-butadiene emulsion (solid content 48%, relative density 0.95).

[0030] A method for preparing an emulsion of anode ceramic slurry for batteries for new energy vehicles is prepared according to the method described in Example 1.

[0031] The emulsions of the battery negative electrode ceramic slurry prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to relevant performance tests. Dispersion stability test: The sample was placed at a temperature of 25°C and a humidity of 55% for 10 days, and the sedimentation state of the sample was observed. The emulsion of the battery negative electrode ceramic slurry was coated on a copper foil. After coating, it was dried (baked at 105°C for 2h), rolled and die-cut to obtain a negative electrode plate. The coating layer thickness was 80μm. The coating effect was observed, and the peel strength, flexibility, plate resistivity, and high temperature capacity retention rate tests were performed; Peel strength test: The sample was cut into a sample with a length of 300mm and a width of 10mm. The sample was fixed on a steel plate with double-sided tape. The steel plate side was inserted into the lower fixing clamp of the lower tensile machine, and the plate side was inserted into the upper fixing clamp. The peel distance was set to 100mm, the peel speed was 100mm / min, and the measurement was recorded. The peeling force during the test; Flexibility test: the test was carried out using a rolling needle experiment, the diameter of the rolling needle was 3.5mm<d<4.5mm, and the cracking of the sample was recorded; Pole sheet resistivity test: the sample was cut into a sample with a diameter of 1.5cm and tested on a BER1300 pole sheet resistance meter; High temperature capacity retention rate test: the conductive electrode ear was welded on the aluminum foil positive pole sheet and the above-mentioned negative pole sheet, and a polyethylene separator was placed between the positive pole sheet and the negative pole sheet, which was wound into a bare battery cell and then wrapped in an aluminum-plastic film, and injected with a volume ratio of EC:EMC:DEC = 1:1:1 (containing 1.0M LiPF 6 ) was used for packaging, and the battery was formed to obtain the battery. The test environment temperature was controlled to be (25±2)℃, and the battery was charged to 4.25V at 0.5C constant current, and then charged to 0.05C at 4.25V constant voltage, and then stood for 10min, and then discharged to 2.8V at 0.5C constant current, and the 25℃ discharge capacity was recorded; then the test environment temperature was controlled to be (60±2)℃, and the battery was charged to 4.25V at 0.5C constant current, and then charged to 0.05C at 4.25V constant voltage, and then stood for 10min, and then discharged to 2.8V at 0.5C constant current, and the 60℃ discharge capacity was recorded, and the high temperature capacity retention rate was calculated, and the calculation formula was: high temperature capacity retention rate (%) = 60℃ discharge capacity / 25℃ discharge capacity × 100%; the above tests were repeated three times and the average value was taken. The test results are shown in Table 1. From the data in Table 1, it can be seen that compared with Comparative Examples 1-2, the emulsion of the negative electrode ceramic slurry for new energy vehicles prepared in Examples 1-4 has better dispersion stability. When the emulsion is applied to the negative electrode substrate, it not only maintains a good coating effect, but also has excellent peeling force and flexibility. In addition, the resistivity and high temperature capacity retention rate of the negative electrode sheet are also greatly improved. From the data in Example 1 and Comparative Examples 1-2, it can be seen that the modified sodium carboxymethyl cellulose prepared by the present invention and the styrene-butadiene emulsion can synergistically enhance the comprehensive performance of the ceramic slurry emulsion.

[0032] Table 1 Emulsion-related performance test results of negative electrode ceramic slurry for new energy vehicles

[0033] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. An emulsion of anode ceramic slurry for a new energy vehicle battery, characterized in that: The method comprises the following raw materials in parts by weight: 80-90 parts of graphite powder, 7-13 parts of alumina powder, 1-3 parts of styrene-butadiene emulsion, and 0.4-0.7 parts of modified sodium carboxymethyl cellulose; The styrene-butadiene emulsion comprises the following raw materials in parts by weight: 25-35 parts of styrene, 20-25 parts of butadiene, 1-3 parts of acrylic acid, 0.5-1 parts of itaconic acid, 0.2-0.5 parts of tert-dodecyl mercaptan, 0.4-0.6 parts of sodium dodecylbenzene sulfonate, 0.5-2 parts of sodium alkylphenol polyoxyethylene ether sulfate, 1-2 parts of acrylamide, 0.4-1 parts of sodium persulfate, 0.1-1 parts of solid alkali, 0.1-0.2 parts of liquid alkali, 40-50 parts of water, 0.5-1.0 parts of defoaming agent and 0.5-1.0 parts of preservative.

2. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 1, characterized in that: The preparation method of the modified sodium carboxymethyl cellulose is: S1. Disperse methyl oleate in anhydrous ethanol under nitrogen atmosphere and stirring, add ethanolamine, mix well, and then dropwise add sodium methoxide methanol solution. The addition is completed within 0.5-1.5 hours, and the temperature is raised to 40-60° C., react for 6-8 hours, and then cool and purify to obtain an intermediate; S2. Disperse 2,5-dimethylhexanoic acid in N,N-dimethylformamide under stirring, add the intermediate obtained in step S1 and p-toluenesulfonic acid, raise the temperature to 75-95° C., react for 6-10 hours, and obtain modified oleic acid ester by cooling and purification; S3, dispersing sodium carboxymethyl cellulose in deionized water, stirring at 55-65°C until dissolved, cooling to room temperature, and then dropping potassium persulfate aqueous solution, the dropping is completed in 40-60 minutes, and stirring is continued for 10-20 minutes, and then adding the modified oleic acid ester obtained in step S2, heating to 70-90°C, stirring and reacting for 2-4 hours, cooling and purifying to obtain modified sodium carboxymethyl cellulose.

3. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 2, characterized in that: In step S1, the mass ratio of methyl oleate to ethanolamine is 10-15:4, the amount of methyl oleate added to the anhydrous ethanol is 0.15-0.20 g / mL, the volume ratio of anhydrous ethanol to the sodium methoxide methanol solution is 40:5-10, and the molar concentration of the sodium methoxide methanol solution is 3.5-4.5 mol / L.

4. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 2, characterized in that: The mass ratio of 2,5-dimethylhexanoic acid, intermediate and p-toluenesulfonic acid in step S2 is 2-3:5:0.08-0.12, and the amount of 2,5-dimethylhexanoic acid added to N,N-dimethylformamide is 0.18-0.26 g / mL.

5. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 2, characterized in that: In step S3, the mass ratio of sodium carboxymethyl cellulose to modified oleate is 1:0.5-0.8, the amount of sodium carboxymethyl cellulose added to the deionized water is 0.08-0.11 g / mL, the volume ratio of the deionized water to the potassium persulfate aqueous solution is 10:0.3-0.5, and the molar concentration of the potassium persulfate aqueous solution is 0.09-0.11 mol / L.

6. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 1, characterized in that: The defoaming agent is polydimethylsiloxane.

7. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 1, characterized in that: The preservative is one or more of phenoxyethanol, ethylhexylglycerin and p-hydroxybenzoic acid.

8. The emulsion of the negative electrode ceramic slurry for the battery for new energy vehicles according to claim 1, characterized in that: The preparation method of the styrene-butadiene emulsion is: (1) Adding acrylic acid, solid alkali and part of sodium dodecylbenzene sulfonate to part of water, stirring until dissolved, to obtain an aqueous phase; (2) adding tert-dodecyl mercaptan to part of styrene and stirring for 20-40 minutes to obtain an oil phase; (3) Under stirring conditions, add sodium alkylphenol polyoxyethylene ether sulfate, acrylamide, itaconic acid, part of butadiene, remaining sodium dodecylbenzene sulfonate and remaining styrene to the remaining water, and after vacuuming, heat to 75-80°C, add part of sodium persulfate, and react at 93-97°C for 20-40 minutes, then add water phase, oil phase, remaining sodium persulfate and remaining butadiene, and keep warm at 95-100°C for 0.5-1.5 hours, and finally add liquid alkali, defoaming agent and preservative, mix well, filter and discharge to obtain the product.

9. The method for preparing an emulsion of anode ceramic slurry for a new energy vehicle battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Disperse modified sodium carboxymethyl cellulose in deionized water, stir at 60-70°C until dissolved, cool to room temperature, add styrene-butadiene emulsion, stir for 15-25 minutes to obtain a mixed emulsion; mechanically solid-phase mix graphite powder and alumina powder to obtain a mixed powder; add the mixed emulsion to the mixed powder, stir for 40-60 minutes, grind, sieve and remove bubbles in vacuum to obtain the product.

Citation Information

Patent Citations

  • Preparation method of ceramic slurry, ceramic diaphragm and lithium ion battery

    CN113087445A

  • Lithium ion battery

    CN101075690A

  • Modified butyl benzene emulsion and preparation thereof

    CN101376682A

  • Negative electrode composite slurry and preparation method thereof, lithium battery negative electrode plate

    CN109768281A

  • Anode slurry and preparation method thereof, and application of anode slurry

    CN110190283A